MANAGEMENT OF WORK PROCEDURES OF THE MINISTRY OF SOCIAL AFFAIRS OF THE REPUBLIC OF INDONESIA FROM THE PERSPECTIVE OF CHANGE MANAGEMENT BASED ON THE MINISTRY OF SOCIAL AFFAIRS REGULATION NUMBER 2 OF 2025 - Kamil, Muhammad Kamil; Abdul Khodir Djaelani; Supriyanto (Pena Cendekia Insani, 2025)
This study examines the organizational transformation of the Indonesian Ministry of Social Affairs (Kemensos) in response to Ministerial Regulation (Permensos) Number 2 of 2025, which implements Presidential Regulation (Perpres) Number 162 of 2024. Shifting from bureaucratic simplification to an emphasis on operational effectiveness and efficiency, this transformation is analyzed using a qualitative method combining document analysis (Permensos 1/2022 and Permensos 2/2025) and in-depth interviews. Key findings indicate the expansion of Kemensos's main structure from eight to ten primary units, notably introducing the Center for Social Welfare Data and Information and the Center for Education, Training, and Professional Development. These changes aim to enhance evidence-based policymaking and strengthen human resource capacity. The restructuring is expected to improve governance through clearer unit functions, faster task implementation, and more professional and accountable service delivery. Theoretically, this study contributes to the discourse on adaptive change management in the public sector. Practically, it offers guidance for governmental reform and serves as a model for other agencies pursuing institutional modernization.